On Tri-α-Open Sets in Fuzzifying Tritopological Spaces - Barah M. Sulaiman; Tahir H. Ismail (Advances in Fuzzy Systems)
In this paper, we introduced and studied (1,2,3)-α-open set, (1,2,3)-α-neighborhood system, (1,2,3)-α-derived, (1,2,3)-α-closure, (1,2,3)-α-interior, (1,2,3)-α-exterior, (1,2,3)-α-boundary, (1,2,3)-α-convergence of nets, and (1,2,3)-α-convergence of filters in fuzzifying tritopological spaces.